PELATIHAN GURU MATEMATIKA DALAM PEMANFAATAN SPSS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN STATISTIKA INFERENSIA - Yulia Isnaeni; Muhammad Iqbal; Aminah Aminah; Salma Farah Nabillah; Nina Kartina; Afrun Akmal; Maria Dewati; Munali Munali (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The use of statistical software in education is a strategic step in strengthening 21st-century competencies within vocational high schools (SMK). This community service program aims to enhance the capacity of mathematics teachers in integrating SPSS software into the teaching of inferential statistics. The program was implemented through a series of stages, including socialization, training, mentoring, and evaluation of SPSS application in the classroom. During the training, teachers were equipped with practical skills in processing and interpreting data using SPSS, as well as developing contextual, technology-based instructional materials. The results of the program indicate a significant improvement in teachers’ ability to use SPSS to support interactive and efficient learning. Program outcomes include the development of an SPSS training module, educational video tutorials, and digital teaching media. This initiative has contributed positively to fostering a technology-oriented learning culture in vocational schools and improving the professionalism of mathematics teachers in teaching inferential statistics.